Melatonin Enhances the Mitochondrial Functionality of Brown Adipose Tissue in Obese-Diabetic Rats - Ahmad Agil; Miguel Navarro-Alarcon; Fatma Abo Zakaib Ali; Ashraf Albrakati; Diego Salagre; Cristina Campoy; Ehab Kotb Elmahallawy (MDPI AG, 2021)
Developing novel drugs/targets remains a major effort toward controlling obesity-related type 2 diabetes (diabesity). Melatonin controls obesity and improves glucose homeostasis in rodents, mainly via the thermogenic effects of increasing the amount of brown adipose tissue (BAT) and increases in mitochondrial mass, amount of UCP1 protein, and thermogenic capacity. Importantly, mitochondria are widely known as a therapeutic target of melatonin; however, direct evidence of melatonin on the function of mitochondria from BAT and the mechanistic pathways underlying these effects remains lacking. This study investigated the effects of melatonin on mitochondrial functions in BAT of Zücker diabetic fatty (ZDF) rats, which are considered a model of obesity-related type 2 diabetes mellitus (T2DM). At five weeks of age, Zücker lean (ZL) and ZDF rats were subdivided into two groups, consisting of control and treated with oral melatonin for six weeks. Mitochondria were isolated from BAT of animals from both groups, using subcellular fractionation techniques, followed by measurement of several mitochondrial parameters, including respiratory control ratio (RCR), phosphorylation coefficient (ADP/O ratio), ATP production, level of mitochondrial nitrites, superoxide dismutase activity, and alteration in the mitochondrial permeability transition pore (mPTP). Interestingly, melatonin increased RCR in mitochondria from brown fat of both ZL and ZDF rats through the reduction of the proton leak component of respiration (state 4). In addition, melatonin improved the ADP/O ratio in obese rats and augmented ATP production in lean rats. Further, melatonin reduced mitochondrial nitrosative and oxidative status by decreasing nitrite levels and increasing superoxide dismutase activity in both groups, as well as inhibited mPTP in mitochondria isolated from brown fat. Taken together, the present data revealed that chronic oral administration of melatonin improved mitochondrial respiration in brown adipocytes, while decreasing oxidative and nitrosative stress and susceptibility of adipocytes to apoptosis in ZDF rats, suggesting a beneficial use in the treatment of diabesity. Further research regarding the molecular mechanisms underlying the effects of melatonin on diabesity is warranted.